PENGARUH KOMPENSASI FINANSIAL DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN (Studi Pada Poltekkes Kemenkes Banjarmasin) - Jauhar Arifin; Hastin Umi Anisah; rini Rahmawati (JWM (JURNAL WAWASAN MANAJEMEN), 2015)
This study aims to know and analyze the simultaneous and partial effect of financial compensation and organizational commitment towards the employee’s performance in Poltekkes Kemenkes Banjarmasin. This study was conducted to 126 employees of Poltekkes Kemenkes Banjarmasin. The employees were sampled by using probability random sampling amounted to 91 employees. This study used quantitative research method that was explanatory. This study used with the object site 126 employees in Poltekkes Kemenkes Banjarmasin which were appointed by using probability random sampling from population. This studies using quantitative research methods that are explanatory research, by sampling of 91 employees. Data collection was conducted to the members of the samples by using questionnaires as research instruments. The collected data were, then, described and analyzed using Multiple Liner Regression technique by using SPSS software ver.19.0 The result of this study concluded that the financial compensation and organizational commitment variables, simultaneously and partially, effected significantly positive towards the employee’s performance in Poltekkes Kemenkes Banjarmasin. The positive relationships from this research show that the financial compensation and organization commitment can improve employee’s performance in Poltekkes Kemenkes Banjarmasin.